2022
DOI: 10.1248/cpb.c21-00901
|View full text |Cite
|
Sign up to set email alerts
|

LC-MS/MS Assay for the Measurement of Cannabidiol Profiling in CBD Oil from Japanese Market and Application for Convertible Tetrahydrocannabinol in Acetic Acid Condition

Abstract: Cannabidiol (CBD), a major non-psychoactive cannabinoid, has a lot of attention due to its potential relaxing properties and led the trend in commercial CBD aroma/oral hemp seed oil from the Japanese market. In this study, a routine assay for evaluating CBD oil samples was performed using LC coupled with tandem mass spectrometry (LC-MS/MS) and was used to apply the convertible tetrahydrocannabinol (THC) in acetic acid conditions. Based on the electrospray positive ion mode, the detection of cannabidiolic acid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…Gas chromatography would be insufficient to monitor CBD oil products according to the current narcotic laws to trace THC (undetected THC in the product) by Japanese investigators. Thus, our studies used an LC technique that did not convert CBD to trace THC while the instrument operated (Takashina et al, 2020; Takashina et al, 2022). Furthermore, it is difficult to separate these cannabinoids, especially CBDA and CBGA, CBG and CBD, and Δ 9 ‐THC and Δ 8 ‐THC using the C 18 column.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Gas chromatography would be insufficient to monitor CBD oil products according to the current narcotic laws to trace THC (undetected THC in the product) by Japanese investigators. Thus, our studies used an LC technique that did not convert CBD to trace THC while the instrument operated (Takashina et al, 2020; Takashina et al, 2022). Furthermore, it is difficult to separate these cannabinoids, especially CBDA and CBGA, CBG and CBD, and Δ 9 ‐THC and Δ 8 ‐THC using the C 18 column.…”
Section: Resultsmentioning
confidence: 99%
“…The Japanese Minister of Health, Labour and Welfare investigated these distributed CBD oil products and THC was detected (undisclosed quantitative values). Thus, we validate the evidence of the adequacy as follows: (1) an analytical strategy based on chromatographic technique is needed for an accurate and simple procedure (Tsujikawa et al, 2022, and Supporting Information); (2) the limit of quantification (LOQ) value should be indicated for high CBD contents and trace amounts of THC/other cannabinoids in oil products (Azorín et al, 2023); and (3) CBD stability should be investigated for the convertible THC in oil products with various additives at high temperatures (Takashina et al, 2022, and Supporting Information). Moreover, we have improved the liquid chromatography–tandem mass spectrometry (LC–MS/MS) assay by adding Δ 8 ‐THC and tetrahydrocannabivarin (THCV), which is a pharmacological isomer warned to be harmful (Abioye et al, 2020, and Supporting Information).…”
Section: Introductionmentioning
confidence: 99%
“…Current research on cannabis products focuses mainly on determining the contents of cannabinoids that occur naturally in cannabis, usually covering up to a dozen compounds at a time [ 27 , 34 , 36 , 37 , 38 , 46 , 47 ]. Heo et al [ 33 ] published a method used for the determination of ∆9-tetrahydrocannabinol (THC) and eight synthetic cannabinoids, indicating that compounds of this type were detected by the Korean Customs Service in herbal products and dietary supplements in 2012.…”
Section: Resultsmentioning
confidence: 99%
“…In turn, Heo et al [ 33 ] developed the LC–ESI–MS/MS method for the determination of natural and synthetic cannabinoids in food, herbs, and dietary supplements, in the form of capsules, tablets, liquids, cookies, and candies. The use of this technique in the analysis of cannabinoids in cannabis-based food products has also been described by some authors [ 34 , 35 , 36 , 37 , 38 , 39 , 40 ]. Research in the field of forensics demonstrates that these products most often appear on the market in the form of fortified plant materials that are indistinguishable from hemp for an average consumer.…”
Section: Introductionmentioning
confidence: 99%
“…Takahashi et al showed that oral administration of a liposome-encapsulated CBD to rats could significantly increase the bioavailability and cellular uptake efficiency of CBD compared to free CBD. [39] The pharmacokinetics in vivo revealed that CBD-entrapped nano-particles demonstrate at least a 9-fold increase in oral bioavailability when compared to CBD administered with piperine as an absorption enhancer. [40][41][42] PLGA is widely used as a drug carrier due to its biodegradable and drug control release characteristic.…”
Section: Discussionmentioning
confidence: 99%